Experiences of parents whose school‐aged children were treated with therapeutic hypothermia as newborns: A focus group study - Sari Kokkonen Nassef; Mats Blennow Bohlin; Maria Jirwe (Wiley, 2023)
Abstract Aim To describe parents' past and present experiences of their newborn infant's therapeutic hypothermia (TH) treatment after perinatal asphyxia 10-13 years after the event. Background Newborn infants are treated with TH following perinatal asphyxia to improve neurodevelopmental outcomes. Design A qualitative descriptive design using focus groups (FGs). Methods Twenty one parents to 15 newborn infants treated with TH between 2007 and 2009 participated in five FGs. The FGs were transcribed verbatim and analysed using framework approach. The SRQR checklist was followed for study reporting. Results Two main categories were identified: hardships and reliefs during TH treatment and struggles of everyday life. Both categories include three subcategories, the first: (1) concern and gratitude for the unrecognized treatment, (2) insufficiency of information and proposed participation and (3) NICU nurses instilled security and hope. The second with subcategories: (1) unprocessed experiences of the TH treatment, (2) later challenges at school and (3) existential and psychological challenges in everyday life. Conclusion TH of their newborns affected the parents psychologically not only during the treatment, but lasted months and years later. Information and communication with health care professionals and school management were inefficient and inadequate. The parents' concerns could be prevented by an improved identification and understanding of the problems and the needs of the infants and their families before discharge. Relevance for Clinical Practice Through more personalized and efficient preparation and communication by the nursing staff before discharge, many of the parents' worries and problems could be reduced. Check‐up of parents' needs of psychosocial support before and after discharge and offering counselling should become routine. Also, nurses at Well‐Baby Clinics and in school health care should receive knowledge about TH treatment and the challenges the children and the parents experience. Patient or Public Contribution Participation of parents was limited to the data provided through interviews.